Coronary anomaly with a left ventricular accessory chamber: Is it left ventricular aneurysm or diverticulum? - Panduranga, Prashanth (2012)
A 60-year-old male hypertensive was suspected to have post myocardial infarction left ventricular aneurysm. His transthoracic echocardiogram performed elsewhere reported an inferior wall left ventricular aneurysm. He was referred for coronary angiography. His coronary angiogram and repeat transthoracic echocardiogram demonstrated an accessory chamber arising from mid-inferior wall synchronously contracting with the left ventricle suggesting a diverticulum. In addition, he had anomalous coronary arteries with coronary artery disease. His electrocardiogram did not reveal any features suggestive of a post infarct aneurysm. This case illustrates the importance of a comprehensive clinical and echocardiographic examination with a broad differential thought process.